An overview on prostate-specific membrane antigen uptake in malignancies other than prostate cancer: A pictorial essay - Jafari, Esmail; Ahmadzadehfar, Hojjat; Dadgar, Habibollah; Assadi, Majid (World Journal of Nuclear Medicine, 2020)
Prostate-specific membrane antigen (PSMA) is a Type II transmembrane glycoprotein which is extremely overexpressed in prostate cancer epithelial cells. Recently, PSMA-targeted small molecule labeled with 68Ga and 99mTc allowed precise molecular imaging of prostate cancer and PSMA-targeted small molecule labeled with 177Lu leads to the development of radionuclide-targeted therapy of prostate cancer. Despite its name, it has been shown that PSMA has been expressed in several malignancies which can be due to significant neovascularization. Present pictorial assay reports the nonspecific tracer uptake in some malignancies during 68Ga-PSMA positron-emission tomography/computed tomography imaging and 99mTc-PSMA scintigraphy.
Keywords: 68Ga-prostate-specific membrane antigen positron-emission tomography/computed tomography; 99mTc-prostate-specific membrane antigen scintigraphy; prostate cancer; prostate-specific membrane antigen and nonspecific uptake